Women Entrepreneurs Using a Value Chain Approach. Doing business with eight women’s groups as direct actors in dual-purpose cattle and vegetable value chains - Vázquez Vasquez, Augusto C.; Castro Rivera, Nubia; Corrales Briceño, Ligia (Catholic Relief Services, 2015)
This publication is the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprise Management, Health, and the Environment (PROGRESA.) This document shares the experience of eight business ventures with women as direct actors in the dairy and vegetable value chains in the municipalities of El Jícaro, Jalapa, Palacagüina, Telpaneca, Ciudad Darío, and La Concordia.